Significance of Crooke's Hyaline Change in Nontumorous Corticotrophs of Patients With Cushing Disease - Akirov, Amit; Larouche, Vincent; Shimon, Ilan; Asa, Sylvia L.; Mete, Ozgur; Sawka, Anna M.; Gentili, Fred; Ezzat, Shereen (Frontiers in Endocrinology, 2021)
Background Glucocorticoid excess in Cushing disease (CD) leads to negative feedback suppression, resulting in Crooke's hyaline change (CC) of nontumorous pituitary corticotrophs. We aimed to determine the predictive value of CC of nontumorous corticotrophs in CD. Methods The retrospective chart review study included patients with clinical, biochemical, radiologic and outcome data and evaluable histopathology specimens from pituitary surgery for CD. The main outcome was remission of CD, defined by clinical features, biochemical testing, and corticosteroid dependency. Results Of 144 CD patients, 60 (50 women, mean age 43.6±14) had clinical follow-up, biochemical data and histopathology specimens that included evaluable nontumorous adenohypophysis. Specimens from 50 patients (83.3%) demonstrated CC in nontumorous corticotrophs, and 10 (16.7%) had no CC (including 3 with corticotroph hyperplasia). One patient with CC was lost to follow-up and one without CC had equivocal outcome results. During a mean (SD) follow-up period of 74.9 months (61.0), recurrent or persistent disease was documented in 18 patients (31.0%), while 40 (69.0%) were in remission. In patients with CC, the remission rate was 73.5% (95% CI, 59.7%-83.7%) (36/49), whereas it was 44.4% (95% CI, 18.9%-73.3%) (4/9) in patients with no CC. The combination of serum cortisol >138 nmol/L within a week of surgery coupled with absence of nontumorous CC greatly improved the prediction of recurrent or persistent disease. Conclusions CC of nontumorous corticotrophs was observed in 83% of patients with CD, and most patients with CC experienced remission. Absence of CC in nontumorous corticotrophs may serve as a predictor of reduced remission in patients with CD.